2004
DOI: 10.1002/aheh.200300534
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use Effects on Anion‐associated Cation Leaching in Response to Above‐normal Precipitation

Abstract: Fertilizers and liming agents are generally used to achieve optimal economic yields. However, several negative effects of long‐term annual fertilization of nitrogen (N) in particular have been observed, such as reduced cation exchange capacity and decreased base saturation, which may stimulate accelerated leaching loss of other nutrients. Equilibrium‐tension lysimeters installed at a depth of 1.4 m were used to evaluate leaching of soil‐solution ionic constituents from a tallgrass prairie restoration and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…McLaren et al (2003) also reported no significant increase in leachate DOC collected at 70 cm after a single application of metal-spiked sewage sludge. The leachate DOC concentrations measured in this study are similar to that reported in leachate under a restored tallgrass prairie (3.1 mg DOC L 21 ; Brye and Norman, 2004). These observations are also supported by Keller et al (2002) who demonstrated that DOC leaching is not an immediate significant loss mechanism for C applied in organic soil amendments.…”
Section: First-year Response To Litter Treatmentsupporting
confidence: 89%
“…McLaren et al (2003) also reported no significant increase in leachate DOC collected at 70 cm after a single application of metal-spiked sewage sludge. The leachate DOC concentrations measured in this study are similar to that reported in leachate under a restored tallgrass prairie (3.1 mg DOC L 21 ; Brye and Norman, 2004). These observations are also supported by Keller et al (2002) who demonstrated that DOC leaching is not an immediate significant loss mechanism for C applied in organic soil amendments.…”
Section: First-year Response To Litter Treatmentsupporting
confidence: 89%
“…A further difficulty arises from the mobility of Cl − in soils, which intensifies profile leaching of Ca 2 + as a counterion [203][204][205] .…”
Section: ----------------------------------------Kg Ha − 1 ----------mentioning
confidence: 99%
“…Agricultural leaching losses of NO 3 − have toxicological implications for animals and humans (e.g., Camargo and Alonso, 2006) and have generated public concern over escalating costs of compliance with municipal water quality standards. For the producer, NO 3 − leaching represents an economic loss, not only of a valuable nutrient, but also of the exchangeable bases that serve as counterions (e.g., Brye and Norman, 2004). The magnitude of this loss on a regional scale has been well documented for the Mississippi River Basin, with an annual average load of approximately 0.86 Tg of NO 3 − –N between 1996 and 2005 (Aulenbach et al, 2007), nearly threefold higher than the average flux between 1956 and 1965 (Goolsby and Battaglin, 2001) and attributed largely to N fertilization (Mississippi River/Gulf of Mexico Watershed Nutrient Task Force, 2008).…”
mentioning
confidence: 99%